PENGARUH KEBIJAKAN TARIF IMPOR GULA TERHADAP INTEGRASI PASAR GULA DOMESTIK DAN DUNIA - Nugroho Ari Subekti; Anita Carolina (Buletin Ilmiah Litbang Perdagangan, 2011)
this paper aims to analyze the sugar domestic market integration with the world sugar market, and the influence of sugar impor tariff policy towards integration of the domestic and world sugar market. We observe variables namely domestic price sugar (gKP), world raw sugar price (RAW), world white sugar price (ReFINed), import tariff raw sugar (tAXRAW), dan import tariff white sugar (tAXReFINed) during period of 1998.1 - 2010.12. To find the integration of all variables, we use Johansen Cointegration test, Vector Error Correction Model approach that provide us two quantitative measurements, (i) impulse response function; (ii) variance decomposition. this research concludes that all variables have an integration. sugar import tariff imposed by the government were influenced by market integration. The result of impulse response function shows that every variables has response to shock from other variables and the result of variance decomposition. In general, it can be stated that each variable can explain to each other in case of a shock to one variable, but the portion of the explanation of each variable is still dominated by itself. In order to improve the performance of the domestic sugar market, we proposed the following policy recommendations: 1) Increase the number of Listed Importer (It) to reduce the high market concentration; 2) Apply hedging mechanism by using forwards or futures contracts instrument with the longer maturities; 3) encourage revitalization of domestic sugar industry, because the tariff will soon be eliminated in 2015 (AseAN market integration) and 2020 (global market integration).